THE COURSE OF CHRONIC ISCHEMIC PANCREATITIS IN PATIENTS WITH CORONARY HEART DISEASE - Khusainova Munira Alisherovna; Islamova Kamola Akramovna; Otamurodova Khurshidabonu Baxtiyorovna (Ta’lim innovatsiyasi va integratsiyasi, 2024)
The formation of changes in the pancreas in chronic abdominal ischemia is based on a violation of the blood supply to the organ and a change in microcirculation associated with an increase in the concentration of endothelin-1 in the blood and a decrease in nitric oxide metabolites. The aim of the study was to increase the effectiveness of treatment of chronic pancreatitis associated with stenosing atherosclerosis of the abdominal aorta in patients with chronic ischemic heart disease.